Análisis de exportación de aguacate hass entre Colombia y México hacia Emiratos árabes unidos (2022)
This monograph proposes to study the competitive advantages through a distribution and marketing analysis of Colombia's capacity to export hass avocado to the United Arab Emirates. For this purpose, a bibliographic and documentary analysis will be made in the national territory in order to identify which departments generate greater production and the international logistics conditions, in order to identify the competitive capacity that Colombia has compared to Mexico, the country with which it will be compared and who also exports this fruit, as well as the negotiation policies that Colombia has with the United Arab Emirates.